The influence of farmers' business behavior in achieving success with integrated paddy and beef cattle agricultural systems in Indonesia - Rahayu, Dewi Ning; Purnomo, Sutrisno Hadi; Sutrisno, Joko (Asian Journal of Agriculture and Rural Development, 2023)
An integrated agricultural system between paddy and beef cattle can provide more benefits for farmers while maintaining environmental sustainability. This research aims to determine the influence of farmers’ business behavior on achieving success with an integrated farming system between rice and beef cattle in Indonesia. This research was conducted through the purposive sampling of 183 respondents who were rice farmers and beef cattle breeders in Karanganyar Regency. A sample of farmers was selected that had implemented an integrated farming system between paddy and cattle for at least one year. The variables used in this study included individual factors, environmental factors, business behavior, and business performance. The data were analyzed through Structural Equation Modeling (SEM) using AMOS (Analysis of Moment Structure) software. The results showed that farmers’ business behavior could influence farmers’ business performance in achieving success with an integrated farming system between paddy and beef cattle. This study showed that individual factors, environmental factors, and business behavior can increase a farmer’s business performance.